Copper and levonorgestrel containing intrauterine devices: comparison of their effect on oxidative stress markers. (3rd April 2021) - Buyuk, Gul Nihal; Oskovi-Kaplan, Z. Asli; Kansu-Celik, Hatice; Neselioglu, Salim; Erel, Ozcan; Engin-Ustun, Yaprak
Abstract: Objective: We aimed to evaluate the oxidative stress by measuring the thiol-disulfide balance in women who use either T380A or LNG-IUD as a contraceptive method. Material and method: The study included two groups; 30 women with LNG-IUD and 30 women with copper-IUD. Thiol-disulfide homeostasis as a marker of oxidative stress was analyzed before the IUD insertion and on the 6 th month after insertion. Results: The LNG-IUD group had similar native thiol levels with Cu-IUD (293.1 ± 43.5 µmol/l vs. 290.4 ± 42.4 µmol/l respectively, p = 819). In the copper-IUD group total thiol levels were higher than LNG-IUD group (345.5 ± 58.2 µmol/l vs. 319.5 ± 52.4 µmol/l, p = .031). A significant increase was observed after 6 months in LNG-IUD patients in terms of disulfide/native thiol (7.9 ± 4.4% vs. 11.2 ± 2.6%, p = .006), disulfide/total thiol (6.2 ± 1.8% vs. 8.7 ± 1.9%, p = .004) and Native thiol/total thiol (87.1 ± 12.1% vs. 82.3 ± 8.2%, p = .004) levels. After 6 months in copper-IUD patients, disulfide (22.3 ± 7.3 µmol/l vs. 27.5 ± 6.9 µmol/l respectively, p = .006), disulfide/native thiol (7.7 ± 3.8% vs. 9.8 ± 2.4% respectively, p = .007), disulfide/total thiol (6.4 ± 2.03% vs. 8.2 ± 1.8% respectively, p = .007) and native thiol/total thiol (86.3 ± 9.4% vs. 83.8 ± 10.6% respectively, p = .007) levels were increased. Conclusion: An increase in oxidative stress markers were observed in both groups. Studies evaluating the long term subclinical risks of IUD's are needed to understand the outcomes of the increased oxidative stress.